A new species of dragons blood Croton (Euphorbiaceae) from South America with singular inflorescences - Rina, R. (2017)
Croton amentiformis, a new species of Euphorbiaceae from western South America, is described and illustrated. Morphological evidence and data from leaf anatomy indicate that the new species belongs to the dragons blood group (Croton section Cyclostigma). The dense and congested inflorescence is unusual within the genus. This singular dragons blood species is dedicated to the Florence Tropical Herbarium (FT) on the occasion of its 100th Anniversary celebrated in 2014. © 2015 Dipartimento di Biologia, Universit di Firenze